CLONING OF GENE ENCODING THERMOSTABLE ALPHA-AMYLASE OF BACILLUS LICHENIFORMIS SITH - Riany (NIM 105 03 008), Anastasia
ABSTRACT: Bacillus licheniformis alpha-amylase (BLA) cleaves alpha-1,4-glycosidic bond in the inner part of the starch into oligosaccharides, alpha-limit dextrin, and glucose. Since it has a high optimum temperature, BLA is then widely used in liquefaction starch in industry. In order to achieve high level of protein production, the gene encoding alpha-amylase of B. licheniformis SITH (bla) will be expressed in Pichia pastoris. The bla gene was amplified by Polymerase Chain Reaction (PCR), cloned into pGEM-T vector, and subsequently subcloned into P. pastoris expression vector. The amplification of bla using primers which was designed based on published BLA sequence (Acc no. E01158) resulted in 1,4 kb DNA fragment. The resulted 1,4 kb DNA fragment had been cloned into pGEM-T and pPICZ alpha A. Analysis of 1453 bp nucleotide sequence showed that the bla gene has 98% homology compared to the published sequence. Nucleotide deduction sequence analysis shows that there are five amino acids substitutions, namely L134R, L198Y, A250E, S320A, S417T and several mutations in the C-terminal compared to the published sequence. The effect of these mutations on protein stability is then determined in silico by measuring the total energy of protein. The final total energy of published BLA and BLA SITH are -5460.867 kJ/mol and -7347.658 kJ/mol, respectively. This total energy difference indicates that the mutation might lead to the increase of putative isolated alpha-amylase stability.